2009
DOI: 10.1186/1471-2105-10-446
|View full text |Cite
|
Sign up to set email alerts
|

Data mining of enzymes using specific peptides

Abstract: BackgroundPredicting the function of a protein from its sequence is a long-standing challenge of bioinformatic research, typically addressed using either sequence-similarity or sequence-motifs. We employ the novel motif method that consists of Specific Peptides (SPs) that are unique to specific branches of the Enzyme Commission (EC) functional classification. We devise the Data Mining of Enzymes (DME) methodology that allows for searching SPs on arbitrary proteins, determining from its sequence whether a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Accumulatively, eight strings of residues (Peptide 4–11) of KL1 domain of Klotho were marked as making good interactions with Wnt3 and Wnt3a. Furthermore, three new peptides (Peptide 1–3) were also predicted having glycosidase activity using DME 32 . Thus, in total 11 peptides were taken for docking simulations with important domains of Wnt3 and Wnt3a ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulatively, eight strings of residues (Peptide 4–11) of KL1 domain of Klotho were marked as making good interactions with Wnt3 and Wnt3a. Furthermore, three new peptides (Peptide 1–3) were also predicted having glycosidase activity using DME 32 . Thus, in total 11 peptides were taken for docking simulations with important domains of Wnt3 and Wnt3a ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting docked complexes from both docking programs were analyzed to understand interactions of Klotho amino acid residues with Wnt proteins. Furthermore, three new peptides in Klotho’s KL1 domain were predicted by Data Mining for Enzymes Search Utility (DME) which were expected having glycosidase activity 32 .…”
Section: Methodsmentioning
confidence: 99%
“…The SPs are strings of amino acids, derived from enzyme sequences using MEX and showed that the coverage of the SPs is better than that of PROSITE motifs in finding the function of enzyme families. Further, Weingart et al [39] have demonstrated how SPs can be employed on Data Mining of Enzymes (DME) on any given set of protein sequences. They use a peptide length of greater than six for the protein sequences that carried the same EC assignment for better accuracy.…”
Section: Methods By Feature Spacementioning
confidence: 99%
“…lower false positives, by recognizing functionally inconsistent differences among key residues. Several sequence motif-based algorithms were designed specifically for this task, including Confunc 28 , DME 29 , and EFICAz2 30 . All rely on discovering discriminatory sequence fragments shared by proteins with identical function and not others.…”
Section: Sequence-based Patternsmentioning
confidence: 99%